2011
DOI: 10.2337/db10-0426
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon Receptor Knockout Prevents Insulin-Deficient Type 1 Diabetes in Mice

Abstract: OBJECTIVETo determine the role of glucagon action in the metabolic phenotype of untreated insulin deficiency.RESEARCH DESIGN AND METHODSWe compared pertinent clinical and metabolic parameters in glucagon receptor-null (Gcgr−/−) mice and wild-type (Gcgr+/+) controls after equivalent destruction of β-cells. We used a double dose of streptozotocin to maximize β-cell destruction.RESULTSGcgr+/+ mice became hyperglycemic (>500 mg/dL), hyperketonemic, polyuric, and cachectic and had to be killed after 6 weeks. Despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
293
4
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(311 citation statements)
references
References 41 publications
11
293
4
3
Order By: Relevance
“…Loss of this paracrine inhibition in diabetes promotes hypersecretion of glucagon, and the hyperglycemia and hyperketonemia of diabetes classically thought to be a consequence of blunted insulin signaling are mediated, in part, by excess glucagon (Brand et al 1996, Lee et al 2011, Unger & Cherrington 2012. Therefore, abnormal alphacell function and an increased glucagon:insulin ratio are central to the pathology of fatty liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of this paracrine inhibition in diabetes promotes hypersecretion of glucagon, and the hyperglycemia and hyperketonemia of diabetes classically thought to be a consequence of blunted insulin signaling are mediated, in part, by excess glucagon (Brand et al 1996, Lee et al 2011, Unger & Cherrington 2012. Therefore, abnormal alphacell function and an increased glucagon:insulin ratio are central to the pathology of fatty liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of the opposing action of insulin, this results in unrestricted hepatic gluconeogenesis and glycogenolysis, resulting in high blood glucose levels and contributing to diabetic ketoacidosis. Recently, a study reported that deleting the glucagon receptor, and therefore eliminating glucagon action, after streptozotocin-induced β-cell destruction in mice normalized fasting blood glucose concentrations and lowered free fatty acid levels [7]. Thus, blocking glucagon action might also be helpful in preventing and treating diabetic ketoacidosis.…”
mentioning
confidence: 99%
“…The discovery that hyperglycemia could result from increased glucagon production in pancreatic a-cells and other tissues renewed interest in this hormone (21)(22)(23), particularly when glucagon suppression restored normoglycemia (24). Accordingly, mice with genetic ablation of glucagon signaling have improved peripheral insulin sensitivity (25,26) and are protected against both type 1 and type 2 models of diabetes (27,28). In both settings, hyperglycemia is prevented primarily by reduced glucagon-mediated hepatic glucose production.…”
Section: Discussionmentioning
confidence: 99%